Pendidikan Nilai Karakter Dan Spiritual Berbasis Komunitas di MI Miftahul Huda Dono-Sendang Kabupaten Tulungagung - Meyta Dewi Anggarwati (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2019)
The essence of education is basically not only a matter of transfer of knowledge, but also the transfer of values, in the sense that sticking values and practices will be very significant in the formation of noble and good character of students, not just memorizing and knowing. Character education is a very urgent matter to be discussed and further developed both in the theoretical and practical framework, therefore teachers and educators have a clearer picture and deeper knowledge of the experience of institutions that continuously expand in the implementation of education. to achieve good character of students. The problems presented in this study are: how is the implementation of character education in the Miftahul Huda Ibtidaiyah Madrasah. The purpose of this study was: to understand the process of implementing character education at Miftahul Huda Islamic School. This research is a field research with a qualitative approach. The subject of this study was MI Miftahul Huda. The process of collecting data is done by observation and interviews. The results showed that, first, the implementation of character value education in Ibtidaiyah Miftahul Huda Madrasah was basically the development of al-Karimah moral education which was implemented in several aspects.